Who aspires to higher education? Axes of inequality, values of education and higher education aspirations in secondary schools in Luxembourg and the Swiss Canton of Bern. (4th February 2021) - Hadjar, Andreas; Scharf, Jan; Hascher, Tina
Abstract: This article reports a study that investigated secondary school students' higher education aspirations (towards university studies, ISCED 6 and above) and how these differ between student groups as well as how these are impacted by values of education. Panel data of more than 300 secondary school students in two countries, Luxembourg and Switzerland (the Swiss Canton of Bern) was analysed. Schools are structured differently in the education systems of Luxembourg and the Swiss Canton of Bern. The results of our analysis show that students in the Luxembourgish sample more often aspire to higher education than in the Swiss sample. Disparities in higher education aspirations were also more pronounced in the Luxembourgish sample, boys and students from families of low socio‐economic status (SES) were less likely to aspire to higher education. While the effects of values of education are generally scarce, stimulation in terms of anticipated enjoyment and interest derived from participation in higher education seems to have a positive effect on higher education aspirations.